Fake diaries, made up confessions and bespoke faces: the intimate performances of Alan Pauls - Rodriguez Montiel, Víctor Emiliano (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of this paper is to explore and to analyze the strategies of autofiguration to which Alan Pauls appeals to intervene his autobiographical material in La vida descalzo, travelogues and fake diaries. «Life», for a dandi like him, is not understood as a practice of confidence (that is: a search for authenticity, frankness, spontaneity). «Living», for a cinephile like him, is understood in the same way that the universe of cinema understands it: pure performance, montage, simulation. Even though his confessional exercises are not intented to be true, my hypothesis is that these autobiographical practices hide and indirectly shows certain intimate impulses linked to his father, Axel.